Comparative Analysis of Single-Dose and Multiple-Dose Antibiotic Prophylaxis in Preventing Surgical Site Infections - Shanmukha Koppolu; Lathika Suresh; Rakshana Munusamy; A Prashanth; Shoraf Pascal; Alekhya Emandi; Shri Mirunalini Thangaraj; Gaurav Vijayrao Deshmukh (Journal of Pharmacy and Bioallied Sciences)
Background: Surgical site infections (SSIs) represent a significant challenge following general surgical procedures, affecting approximately 1 in 24 patients undergoing inpatient surgery in the United States. Despite advances in antibiotic therapies and antiseptic techniques, SSIs continue to impact surgical outcomes. Effective prophylactic antibiotic administration is critical for reducing SSI rates. This study aims to evaluate the effectiveness of single versus multiple-dose antibiotic prophylaxis in preventing SSIs in clean and clean-contaminated surgical procedures. Methodology: This prospective, comparative study was conducted at the Department of General Surgery, Madha Medical College and Research Institute. A total of 80 individuals receiving general surgical interventions with either sterile or slightly contaminated wounds were included. The sample size was calculated to achieve 95% confidence and 80% power. Patients were randomly assigned to receive either a single dose of antibiotic prophylaxis within 4 hours before surgery (Group A) or multiple doses (one the day before the operation and another 4 hours before the operation) (Group B). Postoperative monitoring was performed from days 3 to 8, with wound swab cultures taken for cases exhibiting signs of infection. Statistical analysis was performed using SPSS, with significance set at P < 0.05. Results: The study found no significant difference in SSI rates between the single-dose and multiple-dose prophylaxis groups. Both groups showed comparable outcomes regarding wound infections and clinical parameters such as patient temperature and wound discharge. The Chi-square test and independent sample t-test revealed no statistically significant differences in infection rates between the two prophylaxis regimens. Conclusion: The findings suggest that a single dose of antibiotic prophylaxis is as effective as multiple doses in preventing SSIs in clean and clean-contaminated surgical procedures. The lack of significant difference in infection rates indicates that single-dose prophylaxis may be a viable alternative to multiple doses, potentially simplifying the prophylaxis protocol and reducing the risk of antibiotic resistance.